Implementation of Strengthening Character Education at SMP Negeri 15 Mataram - Nanda Apridina Nurhaliza; Pian Ramadhani; Mohamad mustari (Penerbit Hellow Pustaka, 2025)
This observational study aims to describe the implementation of Character Education Strengthening (PPK) at SMP Negeri 15 Mataram through intracurricular, cocurricular, and extracurricular activities. Observations were conducted through interviews with school officials and observations of routine programs and character building. The results indicate that the school has implemented the PPK program systematically, referring to the Pancasila Student Profile. Various activities such as Friday Imtak (Friday Prayer), literacy, Scouting, and 24 extracurricular activities serve as the primary means of instilling character values. Challenges faced include differences in student character and minimal family support. The school addresses these through active communication with parents and cross-agency collaboration. This study concludes that PPK implementation is effective, but requires greater support from families.